HUBUNGAN DUKUNGAN KELUARGA DENGAN MOTIVASI BELAJAR PADA MAHASISWA PROGRAM S1 KEPERAWATAN DI STIKES YATSI TANGERANG - Paujiyah, Siti Ika; Embrik, Inna Sholihati; Sentosa, Bambang Merdi (Nusantara Hasana Journal, 2022)
Learning motivation is an encouragement that supports individuals to carry out learning activities that make themselves enthusiastic and happy in learning so that goals can be achieved. Many factors can affect learning motivation, one of which is family support. Research objectives to determine the relationship between family support and learning motivation in undergraduate nursing students at STIKes Yatsi Tangerang. This research is quantitative research with quantitative research design with correlation descriptive method. The instrument used is a questionnaire and the analytical test used is the chi square test. Based on the results of the chi square test analysis, it was found that the p-value was 0.002 <0.05, so it can be concluded that Ha is accepted and Ho is rejected, so it can be concluded that there is a significant relationship between family support and student motivation to learn. There is a relationship between family support and learning motivation in undergraduate nursing students at STIKes Yatsi Tangerang.